Cytotoxic oxidovanadium(IV) complexes of tridentate halogen‐substituted Schiff bases: First dinuclear V(IV) complexes with O → VIV = O → VIV = O core. (1st October 2021) - Rudbari, Hadi Amiri; Saadati, Arezoo; Aryaeifar, Mahnaz; Correia, Isabel; Marques, Fernanda; Blacque, Olivier; Micale, Nicola
Graphical abstract: Abstract: The reaction of potentially N, N, O-tridentate Schiff base ligands, Cl-LH, Br-LH, BrCl-LH and H-LH, with [V IV O(acac)2 ] in 2:1 ratio in methanol gave the corresponding mononuclear and dinuclear oxidovanadium(IV) complexes, VO(Cl-L)2 (1), VO(Br-L)2 (2), [(BrCl-L)2 (H2 O)V(μ-O)VO(BrCl-L)2 ] (3) and [(H-L)2 (H2 O)V(μ -O)VO(H-L)2 ] (4), in good yields. The ligands and complexes were fully characterized by elemental analysis and FT-IR spectroscopy. The ligands were also characterized by 1 H NMR spectroscopy. The oxidation state of V(IV)O with d 1 configuration in all synthesized complexes was confirmed by EPR. Moreover, the structures of 2 and 3 were determined by X-ray diffraction (XRD) analysis which revealed them as mono- and dinuclear vanadium(IV) complexes, respectively, with the ligands coordinated as bidentate chelates. The structure of 3 represents the first example of dinuclear V(IV) complex with O → V IV = O → V IV = O core (Cambridge Structural Database (CSD)​, version 5.42, update of May 2021). The cytotoxicity of ligands and complexes was evaluated towards ovarian (A2780), breast (MCF7) and prostate (PC3) cancer cells at 48 h. While ligands showed modest IC50 values (>42 μM), all complexes turned out to be effective in the range 3.9–17.2 μM. In particular, A2780 and MCF7 cell lines were the most sensitive to the newly synthesized V(IV)O complexes.